Perancangan Manajemen Bandwidth Menggunakan PCQ Di SMP Tunas Bangsa - Utari Nurul Fajar Nasution; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Mikrotik has the ability to improve network performance through the RouterOS device. Junior High School named Tunas Bangsa uses a router that has not been configured properly so it has an impact on poor network quality. This is evidenced by the results of the Quality of Service (QOS) measurement from a throughput parameter which is included in the